2010
DOI: 10.1002/jso.21651
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chest computerized tomography in patients with locally advanced mid or lower rectal cancer: Its role in staging and impact on treatment strategy

Abstract: It seems reasonable to perform chest CT for preoperative staging in patients with T3/T4 mid or lower rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…We agree with previous authors that finding indeterminate PNs should not prompt any modification of the treatment plan for primary colorectal cancer [14,17,30,33], but the diagnostic issue becomes particularly important in the patients concerned, because the treatment options that include surgery and chemotherapy, or some combination of them, improve for metastatic disease [34][35][36].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We agree with previous authors that finding indeterminate PNs should not prompt any modification of the treatment plan for primary colorectal cancer [14,17,30,33], but the diagnostic issue becomes particularly important in the patients concerned, because the treatment options that include surgery and chemotherapy, or some combination of them, improve for metastatic disease [34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, PET/CT can usually only detect nodules more than 10 mm in size [18]; percutaneous needle biopsy may be impossible or uninformative for the purposes of an accurate pathological diagnosis, depending on the size and site of nodules [31]; and video-assisted thoracoscopic biopsy is too invasive to be performed routinely [32]. Chest CT revealed growing nodules in a larger proportion of patients in our series (19/92; 20.6 %) than in other published studies, where the overall rate of ultimate diagnosis of malignancy ranged from 6.3 to 16.6 % in colorectal cancer patients found to have PNs [14,30,33]. This discrepancy may be influenced by the grounds on which pulmonary metastases are suspected, which frequently rely on inference because no final histological diagnosis is available.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…MRI performed with liver-specific contrast agents has > 90% sensitivity in cases of underlying liver disease (steatosis, cirrhosis) or very small lesions (< 1 cm). For this reason MRI is better than CT for metastasis detection[26]. …”
Section: Radiological Assessmentmentioning
confidence: 99%
“…Frequency was nearly three times higher for patients with rectal cancer than for patients with colon cancer. Smaller studies [42][43][44] have shown isolated lung metastases in 9-18% of patients with rectal cancer; although distant metastases can be identified in other organs including the bone and the brain [38].…”
Section: Introductionmentioning
confidence: 99%